TXS 0506+056, the first cosmic neutrino source, is not a BL Lac - Padovani, P.; Oikonomou, F.; Petropoulou, M.; Giommi, P.; Resconi, E. (Monthly Notices of the Royal Astronomical Society, 2019)
We present evidence that TXS 0506+056, the first plausible non-stellar neutrino source, despite appearances, is not a blazar of the BL Lac type but is instead a masquerading BL Lac, i.e. intrinsically a flat-spectrum radio quasar with hidden broad lines and a standard accretion disc. This reclassification is based on: (1) its radio and O II luminosities; (2) its emission line ratios; (3) its Eddington ratio. We also point out that the synchrotron peak frequency of TXS 0506+056 is more than two orders of magnitude larger than expected by the so-called `blazar sequence', a scenario which has been assumed by some theoretical models predicting neutrino (and cosmic ray) emission from blazars. Finally, we comment on the theoretical implications this reclassification has on the location of the γ-ray emitting region and our understanding of neutrino emission in blazars.
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - High Energy Astrophysical Phenomena; BL Lacertae objects: general; galaxies: active; gamma-rays: galaxies; High Energy Physics - Experiment; High Energy Physics - Phenomenology; neutrinos; radiation mechanisms: non-thermal